Values must be at the heart of responding to loss and damage - McNamara, Karen E.; Clissold, Rachel; Westoby, Ross; Yee, Merewalesi; Mariri, Taputu; Wichman, Vaine; Obed, Viviane L.; Meto, Precilla; Raynes, Elizabeth; Nand, Moleen M. (Frontiers in Climate, 2024)
As climate change worsens, loss and damage will rapidly accelerate, causing tremendous suffering worldwide. Conceptualising loss and damage based on what people value in their everyday lives and what they consider worth preserving in the face of risk needs to be at the centre of policy and funding. This study in three Pacific Island countries utilises a local, values-based approach to explore people's experiences of climate change, including intolerable impacts, to inform locally meaningful priorities for funding, resources, and action. What people value determines what is considered intolerable, tolerable, and acceptable in terms of climate-driven loss and damage, and this can inform which responses should be prioritised and where resources should be allocated to preserve the things that are most important to people.